Incidence and predictors of loss to follow-up among pregnant and lactating women in the Option B+ PMTCT program in Northwestern Ethiopia: a seven-year retrospective cohort study - Melkalem Mamuye Azanaw; Adhanom Gebreegziabher Baraki; Melaku Kindie Yenit (Frontiers Media S.A., 2023)
IntroductionAlthough Ethiopia has implemented the Option B+ program over the past 7 years, loss to follow-up among HIV-positive women remains a major problem for antiretroviral therapy (ART) treatment. This study was conducted to investigate the number of women who dropped out of follow-up after the Option B+ program.MethodsA retrospective follow-up study was conducted among 403 pregnant and lactating women between June 2013 and December 2019 at health facilities in Northwest Ethiopia. The Cox proportional hazards regression model was used to identify predictors of loss to follow-up. The results were reported as hazard ratios with 95% confidence intervals (CIs) at a significance level of p = 0.05.ResultsThe overall incidence rate of loss to follow-up was 9.4 per 1,000 person-months of observation (95% CI: 7.40-11.90). According to the multivariable Cox regression, rural residency [adjusted hazard ratio (AHR): 2.30; 95% CI: 1.08-4.88], being a Muslim religion follower (AHR: 2.44; 95% CI: 1.23-4.81), having no baseline viral load measurement (AHR: 4.21; 95% CI: 2.23-7.96), being on ART before enrolment (AHR: 0.30; 95% CI: 0.15-0.62), having drug side effects (AHR:1.82; 95% CI: 1.01-3.33), same-day ART initiation (AHR: 3.23; 95% CI: 1.53-6.84), and having suboptimal adherence level (AHR: 3.96; 95% CI: 2.18-7.19) were significant predictors of loss to follow-up.ConclusionThe incidence of loss to follow-up is lower as compared to evidence from most African countries but slightly higher than the WHO target. It is better to strengthen and expand viral load measurements for all women and to pay attention to women residing in rural areas with fair or poor adherence levels.